3D Printed Robot Hand Structure Using Four-Bar Linkage Mechanism for Prosthetic Application - Wahit, Mohamad Aizat Abdul; Ahmad, Siti Anom; Marhaban, Mohammad Hamiruce; Wada, Chikamune; Izhar, Lila Iznita (MDPI, 2024)
Indexed by WOS